MAPPING CORRELATION-FUNCTIONS OF SCHWINGER AND AXIAL MODELS - Dutra, Alvaro de Souza [UNESP] (Iop Publishing Ltd, 1993)
We show that all Green's functions of the Schwinger and axial models can be obtained one from the other. In particular, we show that the two models have the same chiral anomaly. Finally it is demonstrated that the Schwinger model can keep gauge invariance for an arbitrary mass, dispensing with an additional gauge group integration.